2000
DOI: 10.1007/bf02258295
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ultrasound for the detection of hepatic metastases during laparoscopic colorectal cancer surgery

Abstract: Laparoscopic ultrasound scan with a flexible-tipped probe permits satisfactory hepatic examination. It is superior to conventional ultrasound scan and seems to be as effective as magnetic resonance imaging, although the latter modality is still required to delineate identified lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 15 publications
2
16
0
3
Order By: Relevance
“…Even with state of the art imaging, additional disease may be found at laparotomy, which might preclude hepatic resection [40]. Staging laparoscopy and laparoscopic ultrasound scan may reduce this risk [41–44]. Direct inspection of the abdominal cavity and liver surface can detect peritoneal deposits and small superficial hepatic lesions, easily missed with other techniques.…”
Section: Stagingmentioning
confidence: 99%
“…Even with state of the art imaging, additional disease may be found at laparotomy, which might preclude hepatic resection [40]. Staging laparoscopy and laparoscopic ultrasound scan may reduce this risk [41–44]. Direct inspection of the abdominal cavity and liver surface can detect peritoneal deposits and small superficial hepatic lesions, easily missed with other techniques.…”
Section: Stagingmentioning
confidence: 99%
“…As for metastatic lesions, Goletti et al [13] found LIOUS to be of value for detecting further liver lesions in 10%-30% of the cases and changing the surgical program in 12%, while Hartley et al [14] found that it helped diagnosis in only 2.6% of the treated patients.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that laparoscopic ultrasound could help to overcome this problem. Hartley et al performed a prospective study to evaluate the accuracy of laparoscopic ultrasound for liver scanning [36]. A total of 76 consecutive patients undergoing laparoscopic colorectal resections for malignancy was recruited.…”
Section: Recommendations Of Staging Laparoscopy For Liver Tumoursmentioning
confidence: 99%